Analisis Faktor Dominan Yang Berpengaruh Pada Peningkatan Produktivitas Tenaga Kerja Industri Perhotelan Gryadi Blue Pasific - Sukamdani, Nugroho Budisatrio (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2013)
PT. Gryadi Blue Pacific is an organization engaged in the hospitality industry that continues  to  grow.  Efforts  to  achieve  these  objectives  find  the dominant  factors  that influence the effectiveness and efficiency of the organization. Labor is a major driver in a service process and determine its current activities of the organization. Utilization of a large workforce is indispensable to the achievement of customer satisfaction expectations of the hotel. To  the  organizations  efforts  done  by identifying  the  factors  that  influence  the increase in labor productivity and find the dominant factor affecting the effectiveness and efficiency of the organization that eventually able to increase work productivity. The steps that can be  performed are : 1). Distributing leaflets questionnaires on labor , 2). Identify the variables that affect the increase in labor productivity and 3). Correlation regression factors that affect labor productivity Preliminary  test  results  on  30  variables  considered  only  contained  only  25 variables that have significant value, while 5 other variables have no significant value to the data exceeds the rate of 0.05%. The end result is a dominant factor influencing the selection  of  variables  strict  enough  salary,  incentives,  awards  for  outstanding,  fair treatment and fair, reliable leadership, loyalty to the organization and the variable effect on labor productivity in PT GBP indicated by R square value is 0.703.Keywords : dominant factors , factor analysis , hospitality organizations